1983
DOI: 10.1002/jcp.1041150313
|View full text |Cite
|
Sign up to set email alerts
|

The effects of thyroparathyroidectomy and 1,25 dihydroxyvitamin D3 on changes in the activities of some cytoplasmic and nuclear protein kinases during liver regeneration

Abstract: Partial hepatectomy (HPX), which proliferatively activates the remaining liver cells, triggered two transient prereplicative surges in the total activities of cytoplasmic types I and II cyclic AMP-dependent protein kinase holoenzymes, and of nuclear catalytic subunits from cyclic AMP-dependent protein kinases. It also induced a transient prereplicative increase in the activities of a nuclear Ca2+-calmodulin-stimulable, protamine-phosphorylating protein kinase, and a nuclear poly(L-lysine)-phosphorylating, 105 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…The hormone 1,25(OH) 2 D 3 , either directly or through its calcaemic effects, also has effects on liver in the absence of the growth promotion that follows hepatectomy. Vitamin D deficiency significantly alters hepatic function (Sikorska et al 1983;Haddad et al 1987;Pahuja et al 1989). The hormone also stimulates the activity of isocitrate lyase and malate synthase, key enzymes in the glyoxylate cycle in the liver (Sikorska et al 1983;Davis et al 1990), increases the activity of the NADPH-dependent cytosolic triiodothyronine-binding protein in rat liver and in dRLh rat hepatoma-derived cells (Hashizume et al 1991) and enhances transferrin synthesis in primary cultures of rat hepatocytes (Taniguchi et al 1990).…”
Section: Discussionmentioning
confidence: 97%
“…The hormone 1,25(OH) 2 D 3 , either directly or through its calcaemic effects, also has effects on liver in the absence of the growth promotion that follows hepatectomy. Vitamin D deficiency significantly alters hepatic function (Sikorska et al 1983;Haddad et al 1987;Pahuja et al 1989). The hormone also stimulates the activity of isocitrate lyase and malate synthase, key enzymes in the glyoxylate cycle in the liver (Sikorska et al 1983;Davis et al 1990), increases the activity of the NADPH-dependent cytosolic triiodothyronine-binding protein in rat liver and in dRLh rat hepatoma-derived cells (Hashizume et al 1991) and enhances transferrin synthesis in primary cultures of rat hepatocytes (Taniguchi et al 1990).…”
Section: Discussionmentioning
confidence: 97%
“…Labeled cultures were washed twice with PBS containing 1 mM methionine, and the cells were scraped into the same buffer and transferred to cold tubes with washings, and finally centrifuged at 150 g for 5 minutes. Radioactivity precipitable by 20% trichloracetic acid was measured in each cell sample as described by Sikorska et al, (1983 Fig, 3. A short burst of pp(j0wS" activity was enough to stimulate were used to determine DNA-synthetic quiescent, serum-deprived tsLA23-NRK cells to transit GI and initiate DNA replication.…”
Section: Hours Of Incubationmentioning
confidence: 99%
“…Baran et al 4,5 have shown that 1,25(OH) 2 D 3 increases intracellular Ca 2ϩ in rat hepatocytes, although the mode of action of the hormone in these studies may be due to a membrane receptor rather than the VDR n . 6 Studies performed in our laboratory 7,8 as well as by Whitfield et al 9,10 indicate that the liver responds to 1,25(OH) 2 D 3 , as indicated by its control of DNA polymerase ␣ activity as well as cytoplasmic and nuclear protein kinases leading to an accelerated regeneration process following two-thirds partial hepatectomy in the rat. The latter observations suggest that 1,25(OH) 2 D 3 has a significant effect on liver cell physiology during the compensatory growth process.…”
mentioning
confidence: 99%